Modeling the Ecological and Phenological Predictors of Fruit Consumption by Gibbons (Hylobates albibarbis). (11th December 2014) - Dillis, Christopher; Beaudrot, Lydia; Feilen, Katie L.; Clink, Dena J.; Wittmer, Heiko U.; Marshall, Andrew J.
Abstract Understanding the ecological interactions between plant reproductive strategies and frugivore feeding behavior can offer insight into the maintenance of tropical forest biodiversity. We examined the role of plant ecological and phenological characteristics in influencing fruit consumption by the White‐bearded gibbon (Hylobates albibarbis) in Gunung Palung National Park, Indonesian Borneo. Gibbons are widespread across Borneo, highly frugivorous and perform important seed dispersal services. We compare multiple models using information criteria to identify the ecological and phenological predictors that most strongly influence gibbon fruit use of 154 plant genera. The most important predictors of resource use were the overall abundance of a genus and the consistency of fruit availability. Plant genera can maintain constant fruit availability as a result of (1) individual stems fruiting often or (2) stems fruiting out of synchrony with each other (asynchrony). Our results demonstrate that gibbons prefer to feed on plant genera that provide consistent fruit availability due to fruiting asynchrony. Because gibbons feed more often on genera that fruit asynchronously, gibbons are more likely to disperse seeds of plant genera with this reproductive strategy. Research on other frugivorous species is needed to determine whether the results for gibbons are generalizable more broadly. Finally, these results suggest that asynchronously fruiting plant genera may be particularly important for habitat restoration in tropical forests designed for frugivore conservation.